Identifying critical differentiation state of MCF-7 cells for breast cancer by dynamical network biomarkers - Chen, Pei; Liu, Rui; Aihara, Kazuyuki; Chen, Luonan (Frontiers in Genetics, 2015)
Identifying the pre-transition state just before a critical transition during a complex biological process is a challenging task, because the state of the system may show neither apparent change nor clear phenomenon before this critical transition during the biological process. By exploring rich correlation information provided by high-throughput data, the dynamical network biomarker (DNB) can identify the pre-transition state. In this work, we apply DNB to detect an early-warning signals of breast cancer on the basis of gene expression data of MCF-7 cell differentiation. We find a number of the related modules and pathways in the samples, which can be used not only as the biomarkers of cancer cells but also as the drug targets. Both functional and pathway enrichment analyses validate the results.